The Place of Portrait Generation in Easel Painting - Temirov Murodjon Temirov; Erkinova Shokhidakhon (International Journal on Integrated Education, 2022)
This scientific article reveals the concept of the portrait genre, nature the importance of searching for character and a deep approach to it, and the ancient look at history. The importance of portraits of great people in the work of artists of our developed country and its analysis in the visual arts is reflected. At the same time, the role of portraiture in the development of the younger generation is reflected in the analysis through images